A two-step aABR regime in neonatal hearing screening: an efficient alternative for remote and poor geographic areas - Qirjazi, Birkena; Dyrmishi, Ervin; Toci, Ervin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Neonatal hearing screening is a standard of care for the neonatal population. Nevertheless, lost to follow-up (LTFU) cases remain an issue for many new and mature programs. This study aims to evaluate the impact of hearing screening using an aABR algorithm in a neonatal population, with a particular focus on its effect on LTFU rates. Methods: This retrospective study analyzed 2,072 infants selected from a total of 2,181 neonates born in the districts of Pogradec and Kukës, Albania, during 2018–2019. Two different newborn hearing screening algorithms were applied: a two-stage aABR protocol in Kukës and a three-stage TEOAE–TEOAE–aABR protocol in Pogradec. The “fail” rates and the proportion of infants LTFU were calculated and compared between the two screening approaches. Results: LTFU rates were highest in Pogradec, where a traditional screening algorithm was used, increasing from 1.4% at the first test to 16.9% at the second. In Kukes, the corresponding rates were 0.7% and 15.5%. Fail rates ranged from 22.9% in Pogradec to 6.8% in Kukes. At both sites, fewer neonates failed the second screening than the first. Conclusions: The algorithm based on two aABR stages appeared to produce a lower number of subjects who failed the first screening test and also a reduced number of LTFP cases. The ‘fail’ rates remained high in both sites, although lower in Kukes. Targeted strategies to reduce LTFU should be implemented to enhance the overall sensitivity and effectiveness of the hearing screening program.